Dakwah Multikultural - Zaprulkhan Zaprulkhan (Faculty of Da’wa and Islamic Communication, State Institute for Islamic Studies of Syaikh Abdurrahman Siddik Bangka Belitung, 2017)
Factually, Indonesia is a nation that has a variety of ethnic, linguistic, class, color, and religion that become the nation's assets in forming social harmony. In the study of contemporary political theory, the diversity of human society in all its aspects is also called multicultural society. In religious context, some religious people always socialize their religious teachings to plural society by ignoring the plurality of people's lives in all its aspects. This is where the significance of a multicultural perspective needs to be possessed by anyone who wants to convey religious messages in a multicultural society. From a multicultural perspective, the delivery of religious messages or da'wah requires a preacher to understand the cultural diversity of society and to be positive about the diversity. Multicultural preaching means seeking to create harmony in the midst of diverse societies and still be able to control oneself and tolerate all kinds of unequal differences. This article discusses the multicultural da'wah through the study of Islamic doctrine that is through the perspective of interpretation in order to obtain a more holistic view of the Qur'anic point.